Farmers' perceptions and management of risk in rice-based farming systems of south-west coastal Bangladesh. (July 2019) - Kabir, Md. Jahangir; Cramb, Rob; Alauddin, Mohammad; Gaydon, Donald S.
Highlights: Farmers have clear perceptions of production and market risks. Shortage of irrigation, uncertain rainfall, and price fluctuation are major risks. A range of production, market, and management strategies help to mitigate risk. Trend is to farm and livelihood diversification, supporting household resilience. Policy to safeguard agricultural environment is crucial to sustaining resilience. Abstract: Farmers in coastal Bangladesh face significant production and market risks as well as uncertainty about trends in the farming environment. Understanding farmers' perceptions of the risks they currently experience and the farming and livelihood strategies they adopt to mitigate risk is important to inform policies designed to safeguard coastal livelihoods in the future. In this paper, we draw on a case study of typical village in the coastal zone to explore (1) farmers' perceptions of the cropping risks they face, (2) the implications of risk for the choice of cropping strategies within different farm types, and (3) the role of other farm and non-farm activities in mitigating risk to household livelihoods. Quantitative and qualitative farm-level data were collected through a reconnaissance survey, a village census, a household survey, and household case studies. Farmers saw the shortage of irrigation water in the dry season and uncertain weather patterns as the major sources of production risk. The main source of market risk was the fluctuation in farm-gate demand and prices for dry-season cash crops. Representative budgets were constructed for the major cropping systems practised by small, medium, and large farm households. The riskiness of these systems was simulated, based on farmers' estimates of yield and price variability, and a stochastic efficiency analysis was undertaken. The current systems appeared economically viable given the typical range of yields and prices. While some were riskier than others, farm households were largely able to balance their livelihood portfolios to offset the risks. Major risk management strategies included adoption of stress-tolerant rice varieties, staggering the sale of rice, using early wet season rice as a buffer, switching from rice to non-rice crops in the dry season, and undertaking off- or non-farm employment within and outside the village. The dominant trend was to farm and livelihood diversification, contributing to household resilience. However, at the village level, public policy to safeguard the agricultural environment will be crucial to sustaining household risk management strategies.